Evaluation of the Accuracy of “Ottawa Ankle Rules” for Predicting Fractures in Acute Ankle and Midfoot Injuries - Dwivedi, R; Ale, SB (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Twisting injuries of ankle and foot are one of the most common injuries seen in emergency department and are the most common sports injuries. Almost all such cases are investigated by X-rays to rule out fractures, but clinically significant fractures are detected only in a small number of cases (approximately 15%). Ottawa Ankle Rules (OARs) are screening tools, applied in acute ankle and foot injuries to exclude those cases that are not likely to have fractures and thereby reduce the number of unnecessary X-rays. At the same time, all clinically significant fractures are included and not a single clinically significant fracture is missed when OARs are applied properly. This study was conducted to evaluate the accuracy of “Ottawa Ankle Rules” in our setup. METHODS: This prospective study was conducted in the Emergency and Orthopaedics Department of Lumbini Medical College Teaching Hospital, Palpa. Eighty patients were included in this study. Fifty one patients were in ankle group and 30 patients were in midfoot group. All patients were sent for X-rays after evaluating them according to OARs. RESULTS: Among 81 cases, 13 clinically significant fractures were detected. Sensitivity of the OARs for detecting fractures was 100%. Specificity of the OARs for detecting fractures was 36.76 % for combined ankle and midfoot zones, 36.36% for the ankle zone, and 37.5% for the midfoot zone. Negative predictive value was calculated as 1(100%). Potential of OARs to reduce unnecessary radiographs was calculated 30.86%. CONCLUSION: OARs are very accurate and highly sensitive tools for detecting fractures in acute ankle and midfoot injuries. Implementation of these rules would lead to significant reduction in the number of radiographs and thereby reduce the cost of the treatment, radiation exposure and waiting time of patients at hospital. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11166 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 2-5